Haunting on the Hill - Hand, Elizabeth (London Sphere (Hachette India), 2023)
Playwright Holly Sherwin is close to her big break. Having received a grant to develop her new play, all she needs is time and space to bring her vision to life. Then on a weekend away, she stumbles upon Hill House - an ornate if crumbling gothic mansion, near-hidden outside a small town. Soon Holly's troupe of actors - each with ghosts of their own - arrive at Hill House for a creative retreat. But before long they find themselves at odds not just with one another, but with the house itself.
Keywords: English- Fiction; Horror Fiction